Tiketing Gangguan Teknis Pada Layanan Indihome PT. Telkom Akses Gaharu Medan - Leli, Nur; Ramadhani, Sri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Along with the growing role of the Department of Information Technology (IT) in supporting the company's business processes, accompanied by increased demand for solving IT service disruption. Increased demand for services towards solving IT disruption resulted in piling work of IT Department. Therefore we need a system of management that all requests from the user can be served and well-documented. Web-based trouble ticket is one of the ways that can be used to overcome the problem of the management of the service interruption. Trouble ticket is a report form to disruption of IT services to be taken in response to disturbances. Implementation of information system management of IT service disruption using a trouble ticket with web-based technology allows the reporting process and monitoring the status report can be done in various disorders of IT devices. Management information system IT service disruption using a trouble ticket can improve services to users, beside is a good documentation for the Information Technology Department.